2012
DOI: 10.1080/10810730.2012.666625
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health Information Needs and Gaps in the Health Care System in Uttar Pradesh, India

Abstract: Health information and the channels that facilitate the flow and exchange of this information to and among health care providers are key elements of a strong health system that offers high-quality services,yet few studies have examined how health care workers define, obtain, and apply information in the course of their daily work. To better understand health information needs and barriers across all of levels of the health care system, the authors conducted a needs assessment in Lucknow, Uttar Pradesh, India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…Overall, response rates ranged from 25%–100%, with a median of 65%. In 10 studies, the authors did not acknowledge or address possible biases in their research [25, 26, 29, 31, 37, 39, 4043]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, response rates ranged from 25%–100%, with a median of 65%. In 10 studies, the authors did not acknowledge or address possible biases in their research [25, 26, 29, 31, 37, 39, 4043]. …”
Section: Resultsmentioning
confidence: 99%
“…Information needs were defined as the types of information that public health workers need in their daily work. Several studies reported that public health workers need statistics, government reports and guidelines, and journal articles [11, 27, 31, 40, 42, 46, 48]. Staying current with the latest public health research, finding data, and finding materials for grant-writing were other areas of need [11, 13, 14, 32, 33, 49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group 3 (yellow) includes primary care research, training and education [98-100], quality of care [101,102], quality improvement [103], patient safety improvement and management [104], primary care expenditure [105], general practitioner [106], contribution of primary care to health systems and health [68], primary care reform and evaluation, family medicine [107,108], health literacy [67,109,110], chronic disease management [111], and integrated care.…”
Section: Resultsmentioning
confidence: 99%